REPRESENTASI DAKWAH ISLAM DALAM NOVEL DAN FILM BUYA HAMKA: KAJIAN SASTRA BANDINGAN - Helda Nur Azizah; Yulianeta Yulianeta; Yostiani Noor Asmi Harini (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
The aim of this research is to describe the struggle and spread of Islam in the novel Buya Hamka by Ahmad Fuadi and the film Buya Hamka directed by Fajar Bustomi. This research uses a qualitative descriptive method. The method used in this research is the content analysis method which is a method oriented towards researching the issue of a research object. The data sources for this research are the film Buya Hamka directed by Fajar Bustomi and the novel Buya Hamka by Ahmad Fuadi. The data collection techniques used are reading, listening, screen capture techniques, the main data is the film and novel Buya Hamka. The research results show that the storyline in the novel and film is not detailed because it adjusts to the duration, there are more settings in the novel than in the film, the socio-cultural background in the novel is more detailed than in the film, the number of characters in the novel is less than the number of characters in the film, but the main characters are the same, namely Buya Hamka and Siti Raham.